Textbook of pericyclic reactions - Majumdar, Krishna Chandra; Biswas, Paritosh; Majumdar, Krishna Chandra (New Delhi, Medtech, 2015)
It is readable by any undergraduate or graduate student in physics, mathematics, computer science, chemistry or engineering
Index 223-226p.
Keywords: Cycloaddition reactions; Sigmatropic reactions; Chemistry